Biomimetic dual sensing polymer nanocomposite for biomedical applications - Omar, Abdalla M.; Hassan, Mohamed H.; Daskalakis, Evangelos; Smith, Albert; Donoghue, Jack; Mirihanage, Wajira; Bartolo, Paulo J. D. S. (Frontiers in Bioengineering and Biotechnology, 2024)
There is a growing need for sensing materials that can provide multiple sensing capabilities for wearable devices, implantable sensors, and diagnostics tools. As complex human physiology requires materials that can simultaneously detect and respond to slow and fast pressure fluctuations. Mimicking the slow adaptive (SA) and fast adaptive mechanoreceptors in skin can lead to the development of dual sensing electrospun polymer nanocomposites for biomedical applications. These dual sensing nanocomposites can provide simultaneous sensing of both slow and fast pressure fluctuations, making them ideal for applications such as monitoring vital signs, detecting a wider range of movements and pressures. Here we develop a novel dual sensing PVDF-HFP-based nanocomposite that combines the advantages of capacitive and piezoelectric properties through controling electrospinning environment and processing parameters, polymer solution composition, and addition of nucleating agents such as Carbon Black (CB) to enhance the crystalline development of β-phase, fibre thickness, and morphology. The developed PVDF-HFP/CB nanocomposite presents and response to both slow and fast pressure fluctuations with high capacitance (5.37 nF) and output voltage (1.51 V) allowing for accurate and reliable measurements.